2016
DOI: 10.1371/journal.pone.0156490
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Colonization and Expression of Pathogenicity Related Genes in Fusarium oxysporum f.sp. ciceri during Chickpea Vascular Wilt Disease Progression

Abstract: Fusarium wilt caused by Fusarium oxysporum f.sp. ciceri (Foc) is a constant threat to chickpea productivity in several parts of the world. Understanding the molecular basis of chickpea-Foc interaction is necessary to improve chickpea resistance to Foc and thereby the productivity of chickpea. We transformed Foc race 2 using green fluorescent protein (GFP) gene and used it to characterize pathogen progression and colonization in wilt-susceptible (JG62) and wilt-resistant (Digvijay) chickpea cultivars using conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…They were wrapped in wet sterile muslin cloth till sprouting and transferred to surface-sterilized plastic cups containing autoclaved Soil Rite (mixture of 75% Irish Peatmoss and 25% horticulture grade Expanded Perlite; obtained from M/s Naik Krushi Udyog, Pune, India). The plants were grown for one week in growth chamber (14 h light/10 h dark, 22–25 °C, 50–60% relative humidity) and inoculated with standard Foc races 1, 2 and 4 as described in our previous study 8 . Seedlings treated with sterile deionized water served as controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They were wrapped in wet sterile muslin cloth till sprouting and transferred to surface-sterilized plastic cups containing autoclaved Soil Rite (mixture of 75% Irish Peatmoss and 25% horticulture grade Expanded Perlite; obtained from M/s Naik Krushi Udyog, Pune, India). The plants were grown for one week in growth chamber (14 h light/10 h dark, 22–25 °C, 50–60% relative humidity) and inoculated with standard Foc races 1, 2 and 4 as described in our previous study 8 . Seedlings treated with sterile deionized water served as controls.…”
Section: Methodsmentioning
confidence: 99%
“…The proteomics and metabolomics approaches highlighted up-regulation of several metabolic pathways such as biosynthesis of flavonoids, isoflavonoids, phenylpropanoids, etc. in the resistant cultivar 6 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to Forc016_HCT#1, Fom-derived HCT strains did not cause disease on cucumber Fo was delayed compared to colonization of susceptible plants, and only the lower hypocotyl was colonized (Zvirin et al, 2010) or only root xylem vessels were colonized (Li et al, 2014). In other studies, colonization of xylem vessels of resistant plant roots by Fo was not observed (Cohen et al, 2015;Upasani et al, 2016). In the present study, colonization of the hypocotyl of cucumber and watermelon plants by Fom005_GFP was also not observed, suggesting strong defence responses of nonhosts cucumber and watermelon at the root-stem transition.…”
Section: F I G U R Ementioning
confidence: 78%
“…Eventually the fungus reaches the xylem vessels of the roots and then spreads to the main root and stem in susceptible plants . In resistant plants, however, the fungus is mostly restricted to epidermal cells and the cortex (Upasani et al, 2016). Colonization patterns of compatible or incompatible interactions between Fo and its host plants has been investigated in several ff.…”
mentioning
confidence: 99%
See 1 more Smart Citation